Pathophysiology and Imaging Diagnosis of Acute Mesenteric Ischemia - Sandstrom, Claire K. (Digestive Disease Interventions, 2018)
Acute mesenteric ischemia is a potentially life-threatening condition associated with high mortality, particularly with any delay in treatment. Prompt diagnosis with imaging is crucial to achieve a favorable outcome. Both arterial and venous etiologies can result in ischemia, and the radiologist plays a central role in the initial evaluation of a patient with suspected acute mesenteric ischemia to guide management decisions. This article will review the appropriate imaging evaluation of a patient with suspected acute mesenteric ischemia. The overlapping and the distinguishing findings on imaging, as well as the relevant clinical features, will be discussed for the spectrum of both common and uncommon etiologies of mesenteric ischemia.
Keywords: mesenteric ischemia; mesenteric embolism; mesenteric thrombosis; occlusive mesenteric artery disease; nonocclusive mesenteric ischemia; mesenteric venous thrombosis; superior mesenteric artery; superior mesenteric vein